Remedi Kesulitan Siswa dalam Menyelesaikan Soal Persamaan Kuadrat Bentuk Cerita di Kelas I Sekolah Menengah Kejuruan - Sri Tresnaningsih (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2004)
Pre-test to 34 first-year students of SMKN 03 Malang showed that they had difficulties in solving mathematical problems of narrative square equations. The aim of this qualitative action research was to describe attempts in carrying out remedial teaching to overcome the students’ difficulties in solving such problems. The teaching process of the research was carried out four times as the research action. The results show that the researcher`s efforts in helping the students deal with questions of narrative square equations were successful, which was indicated by the students’ ability to do the questions correctly and by their responses to the interview.